Stakeholders’ Perception of International Public Sector Accounting Standards (Ipsas) in Ondo State Ministry of Finance, Akure: Array - Aribaba, F. O.; Afolabi, Y. A.; Ahmodu, O. A.; Adele, H. A. (Acta Universitatis Danubius. Œconomica, 2020)
The study examines the stakeholders’ perception of International Public Sector Accounting Standards (IPSAS) in Ondo State ministry of finance, Akure. The study employed a survey research design with a population of 410 personnel. The study adopted multi-stage sampling techniques to select the sample size of 116 account personnel. The instrument used for this study was a questionnaire. The questionnaire titled Stakeholders’ Perception of International Public Sector Accounting Standards Questionnaire (SPIPSASQ) designed on Likert scales. This instrument was validated with the reliability coefficient of (.825). Data collected were analysed using Pearson Correlation statistics to test the hypotheses. The study revealed that stakeholders’ perception has a significant relationship with IPSAS implementation at (r .283) while accounting personnel also have a significant relationship with IPSAS implementation at (r .270) with the p-value of (.002 & .003) respectively at 5% level of significance. Based on these findings, the study reveals that the government has not been organized IPSAS training for personnel and the fear of unknown discouraged the staff to support the full implementation of the standards. The study, therefore, recommends that the state commissioner for finance should ensure regular training and compliance of IPSAS standards to enhance government accountability; improve stakeholders’ performance, increase revenue generation and reduce corruption.